Analysis of the error budget for a superconducting undulator SASE line at European XFEL. Issue 1 (1st December 2022) - Marchetti, B.; Casalbuoni, S.; Grattoni, V.; Serkez, S.
Abstract: European XFEL is investing in the development of superconducting undulators (SCUs) for future upgrade of its beamlines. SCUs made of NbTi, working at 2 K, with a period length of 15 mm and a vacuum gap of 5 mm allow covering a range between 54 keV and 100 keV. The effect of mechanical errors in the distribution of the undulator parameter K along the undulators is more relevant for working points at lower photon energy, which are obtained using a higher magnetic field in the undulator. In this article we investigate the effect of error distribution in the K-parameter for a working point at 50 keV photon energy obtained injecting an electron beam with 16.5 GeV energy from the XFEL linear accelerator in a undulator line composed by SCUs with 1.6 T peak magnetic field.